2019
DOI: 10.1111/ijfs.14250
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of oxidative and structural characteristics of proteins, especially lipid transfer protein 1 (LTP1) in beer during forced‐ageing

Abstract: Summary The evolution of oxidative and structural characteristics of proteins, especially lipid transfer protein 1 (LTP1), in beer during forced‐ageing was examined. The oxidative characteristics of beer and proteins were evaluated by DPPH radical scavenging activity and ABTS radical cation scavenging activity. Results showed that the levels of proteins, thiols, LTP1 and antioxidant activity decreased gradually. This was accompanied by the degradation of macromolecular proteins in beer during forced‐ageing. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The ABTS radical scavenging assay was based on the method of Cai et al [23]. ABTS •+ was prepared by reacting colourless ABTS stock solution (7 mM in water) with 2.45 nM potassium persulfate and allowing the reaction to stand for 16 hours in the dark at room temperature.…”
Section: Abts (22 -Azino-bis(3-ethylbenzothiazoline-6-sulfonic Acid)) Radical Scavenging Capacitymentioning
confidence: 99%
“…The ABTS radical scavenging assay was based on the method of Cai et al [23]. ABTS •+ was prepared by reacting colourless ABTS stock solution (7 mM in water) with 2.45 nM potassium persulfate and allowing the reaction to stand for 16 hours in the dark at room temperature.…”
Section: Abts (22 -Azino-bis(3-ethylbenzothiazoline-6-sulfonic Acid)) Radical Scavenging Capacitymentioning
confidence: 99%
“…By 7 days of forced ageing, all protein bands with a DO of 6 mg L À1 almost disappeared. Among them, the protein Z had a molecular weight range of 35-55 kDa, and the LTP1 with the molecular weight around 10 kDa (Cai et al, 2019). The increase in DO in beer caused the disappearance of the LTP1 band under the same ageing condition, which clearly demonstrated that the DO could damage the protein subunit of LTP1.…”
Section: Effect Of Do On Beer Proteins During Forced Ageingmentioning
confidence: 93%
“…After forced ageing for 7 days, the protein content in beer samples with DO of 0.5, 2, 4 and 6 mg L À1 decreased by 15.42%, 16.93%, 20.59% and 22.42%, respectively. The results indicated that the increase of DO might accelerate protein degradation or precipitation, and cause more serious damage to beer when compared with thermal ageing (Cai et al, 2019). Previous studies have shown that the initial DO concentration had a decisive effect on the level of reactive oxygen species (ROS) in beer.…”
Section: Effect Of Do On Beer Proteins During Forced Ageingmentioning
confidence: 97%
See 1 more Smart Citation
“…The high PUFA content of gurum seed oil makes it unstable and prone to oxidation, especially when exposed to light, oxygen and moisture. This oxidative degradation is an issue with vegetable oil products (Cai et al., 2019; Atay & Altan, 2021; Meng et al., 2021) and the nutritional quality of gurum seed oil, affecting its shelf life and sensory properties. In order to overcome these disadvantages, gurum seed oil can be microencapsulated to reduce the oxidation rates, which converts the oil into a powder that can be utilised in food supplements.…”
Section: Introductionmentioning
confidence: 99%